Social marketing nutrition education for low-income population. Issue 5 (4th July 2018) - Hagues, Rachel; Stotz, Sarah; Childers, Austin; Phua, Joe; Hibbs, Judy; Murray, Deborah; Lee, Jung Sun
ABSTRACT: As access to healthy food (or lack thereof) could be considered a social justice issue, social workers should be concerned about this issue and willing to collaborate with colleagues of various disciplines to address it. This study was a formative evaluation conducted to understand best practices, recommendations, and feasibility of a social-marketing-based nutrition education program tailored to the needs of adults with limited income. The authors report findings from focus groups conducted with Cooperative Extension Agents (CEAs) and region coordinators ( n = 45) and Supplemental Nutrition Assistance Program Education (SNAP-Ed) ( n = 69) eligible participants to inform the development of a social marketing nutrition intervention for SNAP-Ed in Georgia. Barriers to healthy eating included cultural preferences, costs of healthy food, lack of time, and lack of availability. Social marketing has a potential to deliver effective and efficient SNAP-Ed targeted to large, limited-resource Georgians. Segmenting the low-income population based on geographical location as well as best methods for outreach can allow tailored messages to meet identified needs, lifestyles, and other variables that make these individuals most likely to respond to the program. Food security and nutrition education are topics of concern for all health care professionals interested in addressing complex health issues of many low-income adults.